Insulating thermally conductive particles, method for manufacturing the same, and insulating thermally conductive polymer
Patent Information
- Application Number
- CN202610298699.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-11
- Filing Date
- 2026-03-12
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]现今电子元件的机壳,或是特殊封装的模塑材料,常通过添加导热的粒子来加强导热的效果,常见是以金属粒子为主,但容易发生金属屏蔽效应,或是短路等问题;若改以陶瓷材料导热粒子,则有添加的比例限制,否则模塑材料会有难以成形的问题,但若添加的比例不够,对于散热的效果提升仍然有限
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of heat conduction, and specifically to an insulating thermally conductive particle, an insulating thermally conductive polymer comprising the same, and a method for manufacturing the insulating thermally conductive particle. Background Technology
[0002] With the development of various electronic components, the increase in high-frequency applications and improved computing power are accompanied by an increase in heat generation. At the same time, the miniaturization and thinning of modern electronic devices have led to reduced internal space and increased component density, making them more susceptible to overheating and failure. Therefore, heat dissipation has become an increasingly important issue.
[0003] Nowadays, the housings of electronic components or the molding materials for special packaging often enhance the heat conduction effect by adding thermally conductive particles. Metal particles are commonly used, but they are prone to metal shielding effects or short circuits. If ceramic thermally conductive particles are used instead, there are limitations on the proportion to be added, otherwise the molding material will be difficult to form. However, if the proportion is not high enough, the improvement in heat dissipation is still limited. Summary of the Invention
[0004] This invention provides an insulating and thermally conductive particle. The insulating and thermally conductive particle comprises cross-linked modified boron nitride. The cross-linked modified boron nitride comprises boron nitride particles, a coupling agent, and a product of the cross-linking agent reaction, wherein the boron nitride accounts for at least 92 wt% of the total weight of the cross-linked modified boron nitride. The coupling agent is selected from the group consisting of oxysilane coupling agents, titanate coupling agents, isocyanate coupling agents, and phosphate ester coupling agents, while the cross-linking agent is selected from the group consisting of aromatic or aliphatic compounds containing two or more reactive functional groups, including carboxy, anhydride, amine, hydroxy, or isocyanate groups. The average particle size of the insulating and thermally conductive particle is 1800 to 4200 nm, and 90% of the total particle size (D90) is less than 6000 nm. The density of the insulating and thermally conductive particle is in the range of 2.8 g / cm³. 3 Up to 3.5g / cm 3 .
[0005] Here, an insulating and thermally conductive polymer is also provided, comprising the aforementioned insulating and thermally conductive particles and a polymer material as a substrate. The insulating and thermally conductive particles are dispersed in the polymer material, accounting for 70 to 90 wt% of the total weight of the insulating and thermally conductive polymer, and the thermal conductivity of the insulating and thermally conductive polymer is greater than 2.25 W / m × K.
[0006] In some embodiments, a method for manufacturing insulating and thermally conductive particles is also provided. The method for manufacturing insulating and thermally conductive particles includes a delamination step, a modification step, a crosslinking step, and a pulverization step. The delamination step involves adding boron nitride particles and a first solvent to a reaction flask and ultrasonically agitating for at least three hours to obtain multiple delamination boron nitride particles. The modification step involves adding a coupling agent to a reaction flask and heating it under reflux with the delamination boron nitride particles to react and obtain multiple modified boron nitride particles. The weight ratio of the coupling agent to the boron nitride particles is 0.01 to 0.1, and the coupling agent is selected from the group consisting of oxysilane coupling agents, titanate coupling agents, isocyanate coupling agents, and phosphate coupling agents.
[0007] The crosslinking step involves adding modified boron nitride particles, a second solvent, and a crosslinking agent to a reaction flask, mixing, and heating under reflux to obtain crosslinked modified boron nitride particles. The weight ratio of the crosslinking agent to the modified boron nitride particles is 0.03 to 0.08. The crosslinking agent is selected from aromatic or aliphatic compounds containing two or more reactive functional groups, including carboxylic, anhydride, amine, hydroxyl, or isocyanate groups. The pulverization step involves removing the crosslinked modified boron nitride particles, drying them, and pulverizing them to obtain multiple insulating and thermally conductive particles with an average particle size of 1800 to 4200 nm and a cumulative particle size (D90) of less than 6000 nm for 90% of the particles. Attached Figure Description
[0008] Figure 1 This is a flowchart of a method for manufacturing insulating and thermally conductive particles.
[0009] Symbol explanation:
[0010] S1: Manufacturing method of insulating and thermally conductive particles
[0011] S10: Delamination Step
[0012] S20: Modification Steps
[0013] S30: Crosslinking Step
[0014] S40: Crushing Step Detailed Implementation
[0015] Exemplary embodiments will now be described in detail with reference to the accompanying drawings to facilitate implementation by those skilled in the art. The overall inventive concept can be embodied in various forms, and is not limited to the exemplary embodiments described herein.
[0016] In addition, the terms "first," "second," and "third" are used only to distinguish one element, component, region, layer, or part from another element, component, region, layer, or part, and do not indicate their necessary order.
[0017] Figure 1 This is a flowchart illustrating a method for manufacturing insulating and thermally conductive particles. Figure 1 As shown, a method S1 for manufacturing insulating and thermally conductive particles is provided herein. The method S1 for manufacturing insulating and thermally conductive particles includes a delamination step S10, a modification step S20, a crosslinking step S30, and a pulverizing step S40.
[0018] Delamination step S10 involves adding boron nitride particles and a first solvent to a reaction flask, followed by agitation in an ultrasonic oscillator for at least three hours to generate delamination boron nitride particles. The agitation disrupts the van der Waals forces between the layers of boron nitride, a change that can be inferred from the increase in the average particle size of the boron nitride. Here, boron nitride can be of different crystal forms, such as hexagonal boron nitride (α-BN), cubic boron nitride (β-BN), zincblende boron nitride, or wurtzite boron nitride.
[0019] The modification step S20 involves adding a coupling agent to a reaction flask and heating it to create a reflux between the coupling agent and the delaminated boron nitride particles. This reflux modifies the surface of the delaminated boron nitride particles, resulting in multiple modified boron nitride particles. The weight ratio of the coupling agent to the boron nitride particles can be from 0.01 to 0.1, for example, 0.01 to 0.08, 0.01 to 0.05, 0.02 to 0.08, or 0.03 to 0.06. The coupling agent contains modifying functional groups selected from the group consisting of siloxane groups, titanate groups, isocyanate groups, and phosphate groups. After modification step S20, the modified boron nitride particles are more plump and have a larger overall particle size than the delaminated boron nitride particles.
[0020] In some embodiments, the modification step is a modification reaction carried out by heating and refluxing at a temperature above 60 degrees Celsius for at least 1.5 hours. However, this is merely an example and not intended to be limiting.
[0021] More specifically, in some embodiments, the coupling agent may be an oxysilane coupling agent, a titanate coupling agent, an isocyanate coupling agent, a phosphate coupling agent, or a combination thereof. For example, the coupling agent may be 3-Aminopropyltriethoxysilane (APTES), γ-3-Aminopropyltriethoxysilane (γAPTES), γ-3-Methacryloxypropyltrimethoxysilane, γ-3-Aminopropyltrimethoxysilane, Vinyltriethoxysilane, (3-Glycidyloxypropyl)trimethoxysilane (GPTMS), Tetra-isopropyl titanate, Tetra-butyl titanate, Toluene diisocyanate (TDI), Methylenediphenyldiisocyanate (MDI), Ethoxy phosphate, or a combination thereof.
[0022] Crosslinking step S30 involves mixing multiple modified boron nitride particles, a second solvent, and a crosslinking agent, causing the crosslinking agent and modified boron nitride particles to undergo a crosslinking reaction. The mixture is then heated (e.g., above 80°C) and refluxed (e.g., for 1.5 hours or more) to obtain crosslinked modified boron nitride particles. Here, the crosslinked modified boron nitride particles can be in large lumps. The weight ratio of the crosslinking agent to the modified boron nitride particles can be from 0.03 to 0.08, for example, from 0.03 to 0.07. The crosslinking agent can be selected from the group consisting of aromatic or aliphatic compounds containing two or more reactive functional groups, including carboxylic acid, anhydride, amine, hydroxyl, or isocyanate groups. The pulverizing step S40 involves removing the crosslinked modified boron nitride particles, drying them, and then pulverizing them to obtain insulating and thermally conductive particles.
[0023] In some embodiments, the first solvent does not react with the coupling agent. For example, in some embodiments, the first solvent may be water, alcohol, isopropanol, acetone, isoacetone, or a combination thereof. The second solvent may be toluene or ethylbenzene.
[0024] More specifically, in some embodiments, the crosslinking agent may be N-(oxiranylmethyl)-N-phenyl-Oxiranemethanamine, 1,3-propanediol, 2,3,4-trimethyl-1,3-pentanediol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, or 1,5-pentanediol. l), 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, ethylene glycol The following are alcohols: glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, tripropylene glycol, glycerol, polyglycerol, ethylene carbonate, and 1,2-propylene carbonate, or combinations thereof.
[0025] Insulating and thermally conductive particles can be obtained through the above manufacturing method. These particles comprise cross-linked modified boron nitride. The cross-linked modified boron nitride comprises boron nitride, a coupling agent, and the product of the reaction between the cross-linking agent and the coupling agent, wherein the boron nitride comprises at least 92 wt% of the total weight of the cross-linked modified boron nitride. The coupling agent is selected from the group consisting of oxysilane coupling agents, titanate coupling agents, isocyanate coupling agents, and phosphate ester coupling agents. The cross-linking agent is selected from the group consisting of aromatic or aliphatic compounds containing two or more reactive functional groups, wherein the reactive functional groups include carboxy groups, anhydride groups, amine groups, hydroxyl groups, or isocyanate groups.
[0026] According to an embodiment of the present invention, the density of the insulating and thermally conductive particles disclosed herein, as determined by density testing, ranges from 2.8 g / cm³. 3 Up to 3.5g / cm 3 .
[0027] Particle size analysis revealed that the average particle size of the insulating and thermally conductive particles ranged from 1800 to 4200 nm, with 90% of the total particle size (D90) being less than 6000 nm. In some embodiments, the average particle size of the insulating and thermally conductive particles was 3750 nm. In some embodiments, 10% of the total particle size (D10) of the insulating and thermally conductive particles was less than 1750 nm, and 50% of the total particle size (D50) was less than 2500 nm.
[0028] In some embodiments, the specific surface area of the insulating thermally conductive particles ranges from 2 to 25 m². 2 / g.
[0029] Furthermore, by incorporating insulating and thermally conductive particles into a polymer material, an insulating and thermally conductive polymer can be obtained. More specifically, the insulating and thermally conductive polymer comprises the aforementioned insulating and thermally conductive particles, as well as a polymer material. The insulating and thermally conductive particles are dispersed in the polymer material, accounting for 50 to 90 wt% (e.g., 70 to 90 wt%) of the total weight of the insulating and thermally conductive polymer, and the thermal conductivity of the insulating and thermally conductive polymer is greater than 2.25 W / m×K.
[0030] In some embodiments, the polymeric material is selected from the group consisting of polydimethylsiloxane (PDMS), thermoplastic polyurethane (TPU), butyl rubber (IIR), ethylene propylene rubber (EPDM), styrene-butadiene rubber (SBR), acrylic rubber (ACM), and fluororubber (FKM).
[0031] In some embodiments, the density of the insulating and thermally conductive polymer is between 2.75 and 3.25 g / cm³. 3 between.
[0032] In some embodiments, the thermal diffusivity of the insulating and thermally conductive polymer is greater than 0.95 mm. 2 / s.
[0033] In some embodiments, the specific heat capacity of the insulating and thermally conductive polymer is between 0.78 and 1.10 J / g×K.
[0034] To make the above-mentioned and other objects, features and advantages of the present invention more apparent and understandable, preferred embodiments are described below in detail with reference to the accompanying drawings.
[0035] Manufacturing of insulating and thermally conductive particles
[0036] Example 1
[0037] First, 15g of hexagonal boron nitride particles and 3kg of 50% IPA aqueous solution were placed in a reaction flask, and then placed in an ultrasonic oscillator for 6 hours to perform the delamination step S10, thereby obtaining delaminated boron nitride.
[0038] Next, epoxypropyltrimethoxysilane ((3-Glycidyloxypropyl)trimethoxysilane, GPTMS) was added to modify the surface of the delaminated boron nitride. The weight ratio of GPTMS to boron nitride was 0.045:1.5. The mixture was heated under reflux for two hours to carry out the modification step S20. After filtration and drying, modified boron nitride particles were obtained.
[0039] Next, 1.5 g of the filtered and dried modified boron nitride particles were mixed with 0.05 g of N-(epoxypropyl)-N-phenyl-epoxyethylene methylamine and added to 100 g of toluene for crosslinking step S30. The mixture was heated under reflux for about two hours. After filtration and drying, the crosslinked modified boron nitride particles were obtained, which were then pulverized using a pulverizer at a speed of 12000 rpm to obtain insulating and thermally conductive particles (I).
[0040] The boron nitride particles obtained in Example 1 at each stage were analyzed using a particle size analyzer (model nanoSAQLA+AS50, Otsuka Technology). The results are shown in Table 1 below.
[0041] Table 1
[0042]
[0043] It is understandable that hexagonal boron nitride particles, after undergoing delamination, modification, and cross-linking processes, result in a larger overall particle structure. This can be verified by the increased particle size of boron nitride particles at each stage, as shown in Table 1. Specifically, hexagonal boron nitride particles account for at least 92 wt% (by weight) of the total cross-linked modified boron nitride, with the remainder being coupling agents or residual components from the reaction between the cross-linking agent and the boron nitride raw material. Furthermore, the increased particle size of boron nitride molecules leads to a decrease in overall density.
[0044] Example 2
[0045] Example 2 was carried out according to the steps and conditions described in Example 1, but 1.5 g of the filtered and dried modified boron nitride particles were mixed and reacted with 0.1 g of N-(epoxypropyl)-N-phenyl-epoxyethylene methylamine. Insulating and thermally conductive particles (II) were obtained.
[0046] Example 3
[0047] The delaminated boron nitride was modified using 3-Aminopropyltriethoxysilane (APTES) as a coupling agent, wherein the weight ratio of APTES to boron nitride was 0.045:1.5. The mixture was heated and refluxed at 80°C for two hours to carry out the modification step S20. After filtration and drying, modified boron nitride particles were obtained.
[0048] Next, 1.5 g of the filtered and dried modified boron nitride particles were mixed with 0.05 g of N-(epoxypropyl)-N-phenyl-epoxyethylene methylamine, and then added to 100 g of toluene for crosslinking step S30. The mixture was heated to reflux at 80 °C for about two hours. Finally, the filtered and dried crosslinked modified boron nitride particles were pulverized in a pulverizer at a speed of 12000 rpm to obtain insulating and thermally conductive particles (III).
[0049] Example 4
[0050] Example 4 was carried out according to the steps and conditions described in Experiment 3, but 1.5 g of filtered and dried modified boron nitride particles were mixed with 0.1 g of N-(epoxypropyl)-N-phenyl-epoxymethylamine and reacted to obtain insulating and thermally conductive particles (IV).
[0051] Manufacturing of insulating and thermally conductive polymers
[0052] Examples 5 to 10
[0053] The above-mentioned insulating and thermally conductive particles (I) to (IV) were mixed in polydimethylsiloxane (PDMS, purchased from Ziyue Silicon Photonics) polymer material with different doping ratios. The proportion of PDMS was adjusted according to the particle filling rate (as shown in Table 2 below) to obtain insulating and thermally conductive polymers (1) to (6).
[0054] Comparative Examples 1 to 6
[0055] Comparative Examples 1 and 2 used modified boron nitride particles from Examples 1 and 3 (reacted with GPTMS and APTES coupling agents, respectively), but without crosslinking, resulting in uncrosslinked modified hexagonal boron nitride particles. Comparative Example 3 used undelaminated, unmodified, and uncrosslinked boron nitride particles. Comparative Examples 4 and 5 used S-BN (S-boron nitride), which consisted of hexagonal boron nitride particles that underwent delamination but were not modified or crosslinked. Comparative Example 6 involved mixing the insulating and thermally conductive particles of the present invention into PDMS, but the particle filling rate was only 60%.
[0056] The test results of the relevant properties of various insulating and thermally conductive particles are shown in Table 2. Density was measured using an Ohaus PX223ZH density meter. First, the liquid (Heptane) density was set, then the weight of the sample in air and the weight of the sample in the liquid were measured to calculate the sample density. Thermal diffusivity was measured using a NETZSCH LFA 447 Laser Flash scanner. First, the sample thickness was measured and dimensions confirmed; then, graphite was uniformly sprayed onto the test sample; finally, the instrument measurement parameters were set, and the thermal diffusivity was calculated using software. Specific heat capacity was measured using a TA DSC 250 specific heat capacity meter. First, the sample was weighed and placed in a platinum pan; then, the DSC heating conditions (20℃ / min) were set and the test was conducted; finally, three data points were measured: an empty pan, a standard (sapphire), and the sample, and the specific heat capacity was calculated using software. Thermal conductivity was calculated using the formula K(W / m×K)=α(mm). 2 / s)×ρ(g / cm 3α × Cp (J / g × K), where α is the thermal diffusivity, ρ is the density, and Cp is the specific heat capacity.
[0057] Table 2
[0058]
[0059] Here, the particle filling rate is defined as the weight percentage of insulating and thermally conductive particles to the insulating and thermally conductive polymer (insulating and thermally conductive particles / (insulating and thermally conductive particles + polymer material) x 100%). Additionally, the insulating and conductive polymer must have a thermal conductivity greater than 2.25 (W / m×K) and a thermal diffusivity greater than 0.95 mm. 2 For a product to be considered worthwhile, its thermal conductivity must be such that the specific heat capacity of the polymer is between 0.78 and 1.10 J / g × K. Comparative Examples 1-6 all failed to meet the thermal conductivity standards (Table 2). (Indicated). In addition, regarding the material ratio, if the filling rate of the insulating thermally conductive particles in the comparative example is increased to slightly more than 75%, for example, to between 78% and 80%, it will result in the polymer being unable to form a film (for example, Comparative Example 5), and it will be impossible to form. Therefore, it is impossible to achieve the desired thermal conductivity effect by filling more thermally conductive particles.
[0060] In summary, by delaminating, modifying, and cross-linking boron nitride particles to create insulating and conductive particles, the spacing between boron nitride layers can be increased (this can be inferred from the increase in the average particle size of boron nitride particles at each stage in Table 1). This makes it easier for the insulating and conductive particles to form bonds with polymer materials and improves the compatibility between the insulating and thermally conductive particles and the polymer materials. As a result, the weight ratio of insulating and thermally conductive particles added to the polymer matrix can reach more than 70%, thereby effectively improving the thermal conductivity of the thermally conductive polymer and enhancing its thermal conductivity properties, making it more suitable for application in high-frequency, high-power electronic devices.
[0061] Although the technical content of the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any modifications and refinements made by those skilled in the art without departing from the spirit of the present invention should be included within the scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the appended claims.
Claims
1. An insulating and thermally conductive particle, comprising: The cross-linked modified boron nitride comprises boron nitride particles, a coupling agent, and a product of the cross-linking agent reaction, wherein the boron nitride particles account for at least 92 wt% of the total weight of the cross-linked modified boron nitride. The coupling agent is selected from the group consisting of oxysilane coupling agents, titanate coupling agents, isocyanate coupling agents and phosphate coupling agents; and the crosslinking agent is selected from the group consisting of aromatic and aliphatic compounds containing two or more reactive functional groups, wherein the reactive functional group includes a carboxyl group, an anhydride group, an amino group, a hydroxyl group or an isocyanate group. The average particle size of the insulating and thermally conductive particles is 1800 to 4200 nm, and 90% of the total particles have a size (D90) of less than 6000 nm.
2. The insulating thermally conductive particles as claimed in claim 1, wherein the average particle size of the insulating thermally conductive particles is 3500 to 4000 nm.
3. The insulating thermally conductive particles as described in claim 1, wherein 10% of the total number of insulating thermally conductive particles has a particle size (D10) of less than 1750 nm, and 50% of the total number of insulating thermally conductive particles has a particle size (D50) of less than 2500 nm.
4. The insulating thermally conductive particles as described in claim 1, wherein the specific surface area of the insulating thermally conductive particles is 2 to 25 m². 2 / g, density is 2.8g / cm³ 3 Up to 3.5g / cm 3 .
5. An insulating and thermally conductive polymer, comprising: A plurality of insulating and thermally conductive particles as described in any one of claims 1 to 4, wherein the insulating and thermally conductive particles account for 70 to 90 wt% of the total weight of the insulating and thermally conductive polymer; and A polymeric material in which the insulating and thermally conductive particles are dispersed within the polymeric material; The thermal conductivity of this insulating and thermally conductive polymer is greater than 2.25 W / m×K.
6. The insulating and thermally conductive polymer as claimed in claim 5, wherein the polymer material is selected from the group consisting of polydimethylsiloxane, thermoplastic polyurethane, butyl rubber, ethylene propylene rubber, styrene-butadiene rubber, acrylic rubber, and fluororubber.
7. The insulating and thermally conductive polymer as described in claim 5, wherein the density of the insulating and thermally conductive polymer is between 2.75 and 3.25 g / cm³. 3 Between these parameters, the thermal diffusivity of the insulating and thermally conductive polymer is greater than 0.95 mm. 2 / s, and the specific heat capacity of the insulating and thermally conductive polymer is between 0.78 and 1.10 J / g×K.
8. The insulating and thermally conductive polymer as claimed in claim 5, wherein the insulating and thermally conductive particles account for 70 to 80 wt% of the total weight of the insulating and thermally conductive polymer.
9. A method for manufacturing insulating and thermally conductive particles, comprising: In the delamination step, multiple boron nitride particles and a first solvent are added to a reactor and ultrasonically vibrated for at least three hours to obtain multiple delamination boron nitride particles. In the modification step, a coupling agent is added to the reactor and heated under reflux with the delaminated boron nitride particles to obtain a plurality of modified boron nitride particles, wherein the weight ratio of the coupling agent to the boron nitride particles is 0.01 to 0.1, and wherein the coupling agent is selected from the group consisting of oxysilane coupling agents, titanate coupling agents, isocyanate coupling agents and phosphate coupling agents; The crosslinking step involves mixing the modified boron nitride particles, a second solvent, and a crosslinking agent, and heating under reflux to obtain crosslinked modified boron nitride particles. The weight ratio of the crosslinking agent to the modified boron nitride particles is 0.03 to 0.
08. The crosslinking agent is selected from the group consisting of aromatic and aliphatic compounds containing two or more reactive functional groups, including carboxyl groups, acid anhydrides, amino groups, hydroxyl groups, or isocyanate groups. as well as In the pulverization step, the cross-linked modified boron nitride particles are taken out, dried, and pulverized to obtain multiple insulating and thermally conductive particles with an average particle size of 1800 to 4200 nm and a cumulative total of 90% of the particles having a size (D90) of less than 5000 to 7000 nm.
10. The method for manufacturing insulating thermally conductive particles as claimed in claim 9, wherein 10% of the total number of insulating thermally conductive particles has a particle size (D10) of less than 1500 to 2000 nm, and 50% of the total number of insulating thermally conductive particles has a particle size (D50) of less than 2000 to 3000 nm.
11. The method for manufacturing insulating and thermally conductive particles as described in claim 9, wherein the first solvent does not react with the coupling agent, and the second solvent is toluene or ethylbenzene.